(3dhGeY GdCacGQ GdeYajIs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s ((3CMeO GdYfGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdeHJOY HdWja MceI eLGQjH GdeUfhYGJ s
(3BNQgG (B:s
(3hajg CjVkG Ef QeJ Cf JSde ef ge hef fcO hGdMeO ddg dhGgH GdYbd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1568s
Keywords: (3GdcjejGA h GdWHjYjGJs